Selective and eco-friendly procedures for the synthesis of Benzimidazole derivatives. The role of Er(OTf)3 catalyst in the reaction selectivity - Herrera Cano, Natividad Carolina (2016)
An improved and greener protocol for the synthesis of benzimidazole derivatives, starting from o-phenylenediamine, with differentaldehydes is reported. Double-condensation products were selectively obtained when Er(OTf)3 was used as the catalyst in the presenceof electron-rich aldehydes. Conversely, the formation of mono-condensation products was the preferred path in absence of thiscatalyst. One of the major advantages of these reactions was the formation of a single product, avoiding extensive isolation andpurification of products, which is frequently associated with these reactions.Theoretical calculations helped to understand the different reactivity established for these reactions. Thus, we found that the chargedensity on the oxygen of the carbonyl group has a significant impact on the reaction pathway. For instance, electron-rich aldehydesbetter coordinate to the catalyst, which favours the addition of the amine group to the carbonyl group, therefore facilitating the formationof double-condensation products.Reactions with aliphatic or aromatic aldehydes were possible, without using organic solvents and in a one-pot procedure with shortreaction time (2?5 min), affording single products in excellent yields (75?99%). This convenient and eco-friendly methodologyoffers numerous benefits with respect to other protocols reported for similar compounds.